Expertise-based systematic guidelines for chiller retrofitting in healthcare facilities - Ahmad, Emy Zairah; Jarimi, Hasila; Mohd Daud, Al Khairi; Razak, Tajul Rosli (Elsevier Ltd, 2023)
Air Conditioning and Mechanical Ventilation (ACMV) generally consume more than half of the energy consumption in commercial buildings in a tropical region. In healthcare facilities, the ACMV systems must comply with the following crucial parameters: indoor air quality, which greatly impacts the thermal comfort of occupants, as well as pressure regime regulations and standards, particularly in critical areas. Due to the high cost of operating the ACMV system, many health facilities in Malaysia have embarked on energy efficiency initiatives. Many have replaced their chillers with magnetic-bearing chiller compressors to benefit from cost reduction. However, despite the replacement, it was found that not all healthcare facilities benefited fully from improved air condition systems other than the higher chillers’ coefficient of performance obtained from the new installation. The paper’s main contribution is to offer a comprehensive and systematic guideline for facility managers to evaluate healthcare facilities ACMV systems and provides solutions that match the healthcare facilities ventilation requirements standards in making effective decision before embarking chiller retrofitting. The proposed guideline is based on the experience and observation of the expertise through energy auditing of the ACMV system and chiller retrofitting evaluation at the healthcare facilities in Malaysia. It may contribute towards more cost-effective management of ACMV system at healthcare facilities in Malaysia while assisting facility managers on chiller retrofitting decision making. More importantly, the guideline has the potential to support sustainable performance of the ACMV system.